The Preferred Locations of Meningioma According to Different Biological Characteristics Based on Voxel-Wise Analysis - Sun, Chongran; Dou, Zhangqi; Wu, Jiawei; Jiang, Biao; Iranmanesh, Yasaman; Yu, Xiaobo; Li, Jianru; Zhou, Hang; Zhong, Chen; Peng, Yucong; Zhuang, Jianfeng; Yu, Qian; et al. (Frontiers in Oncology, 2020)
Objective: Meningiomas presented preferred intracranial distribution, which may reflect potential biological natures. This study aimed to analyze the preferred locations of meningioma according to different biological characteristics. Method: A total of 1107 patients pathologically diagnosed with meningiomas between January 2012 and December 2016 were retrospectively analyzed. Preoperative MRI were normalized, and lesions were semi-automatically segmented. The stereospecifc frequency and p value heatmaps were constructed to compare two biological phenotypes using two-tailed Fisher's exact test. Age, sex, WHO grades, extent of resection (EOR), recurrence, and immunohistochemical markers including p53, Ki67, epithelial membrane antigen (EMA), progesterone receptor (PR) and CD34 were statistically analyzed. Recurrence-free survival (RFS) were analyzed by Kaplan-Meier method. Result: Of 1107 cases, Convexity (20.8%), parasagittal (16.1%) and falx (11.4%) were the most predominant loci of meningiomas. The p value heatmap suggested lesion predominance in the left frontal and occipital convexity among older patients, while in the left sphenoid wing, and right falx, parasellar/cavernous sinus and middle fossa among younger patients. Lesions located at anterior fossa and frontal structures were more frequently seen in the male, while left parietal falx and tentorial regions, and right CPA in the female. Grades II and III lesions presented predominance in the frontal structures compared with grade I ones. Meningiomas at left parasagittal sinus and falx, tentorium, intraventricular regions, and skull-base structures were significantly to receive subtotal resection. Lesions with p53 positivity statistically located at left frontal regions and parasellar/cavernous sinus, higher Ki67 index at the left frontal and bilateral parietal convexity and right parasellar/cavernous sinus, negative EMA at right olfactory groove and left middle fossa, and positive CD34 at the sellar regions and right sphenoid wing. Tumor recurrence rates for grades I, II and III were 2.8%, 7.9%, and 53.8%, respectively. Inferior RFS was observed in older patients, higher Ki67 index, grades II and III, and a larger preoperative volume. Recurrent meningiomas were more frequently found at occipital convexity, tentorium, sellar regions, parasagittal sinus and left sphenoid wing. Conclusion: The preferred locations of meningioma could be observed according to different biological characteristics, which might be helpful for clinical decisions.